A method for assessing ship operability in dynamic ice for independent navigation and escort operations. (1st April 2021) - Lu, Liangliang; Kujala, Pentti; Goerlandt, Floris
Abstract: Ships navigating in ice inevitably encounter different ice conditions. Dynamic ice typically presents severe conditions when it is moving perpendicular towards the parallel midship section, which can lead to ships getting stuck in ice. This can cause delays for ships or even damage to the ship hull. However, there currently is no model to assess ship operability in this dynamic ice. This paper aims to develop a method to assess operability of ships in dynamic ice conditions, which can be used for ship routing to avoid ship stuck. The method is especially useful for emergency response planning purposes, e.g. for marine pollution preparedness and response planning, where an understanding of the operability of response vessels in dynamic ice conditions currently is lacking. First, a transit model is introduced for both independent navigation and escort operations, considering the additional ice resistance by dynamic ice. Then, a ship operability index is proposed based on the modelling of ship's performance. Case studies of independent navigation and escort operations in realistic dynamic ice conditions are investigated to compare with the simulated results. Reasonable agreement is obtained, indicating that the proposed method can be used for ship operability assessment in dynamic ice. Highlights: A transit model for both independent navigation and escort operation in dynamic ice is developed. A ship operability index is proposed based on the modelling of ship's performance. Case studies show reasonable agreement between the simulated model results and empirical observations. Model behaviors are tested in a series of sensitivity analyses. The method is useful for ship routing and emergency response planning to avoid ship stuck in dynamic ice.